Influence of Creativity, Self Efficacy, And Social Skills Toward Performance of Banking Employees - Ina Kurniawati. H; Elisabet Siahaan (TALENTA Publisher, Universitas Sumatera Utara, 2021)
In the era of the Covid-19 pandemic, creativity, self-efficiency andÂ employeeÂ socialÂ skillsÂ are urgently needed. This objective is to determine and analyze creativity, self-efficacy, and social skills on the performance of employees of Bank Muamalat Cabang Balai Kota. The population in this study Â may Â be Â 59 Â employees.Â This Â research Â is Â descriptive Â with Â a Â quantitative Â approach.Â The technique slot deposit 5000 used in the organization and data is multiple linear regression. The results showed that based on the simultaneous test (F-test), it shows that creativity, self-efficacy, and social skills have a significant effect on the performance of employees of Bank Muamalat Cabang Balai Kota. Then based on the partial test (t-test) shows that each variable creativity, self-efficacy